Strategic Gender Egalitarianism in Rural China: The Impacts of Husbands’ Migration on Gender Relations - Zhang, Hong (Am Behav Sci, 2017)
When men migrate for work and couples live separately, structures of gender relations may be altered in response. Our research in rural China about husbands’ and wives’ perceptions of household decision-making and gender-related attitudes examines hypotheses derived from Connell’s (2002) theory of gender relations using the Gansu Survey of Children and Families. Consistent with previous research, we find that both migrant husbands and their wives perceive that women have more decision-making power over household production and consumption. In contrast, the effect of husbands’ migration on their own and their wives’ gender attitudes are less consistent. Both migrant husbands and their wives are more likely than non-migrant spouses to agree that women and men can achieve the same given equal opportunities. Moreover, migrant husbands hold more gender egalitarian views towards their children’s education than non-migrant husbands. However, migrant husband and their wives are no more likely to question sons’ obligations or men’s and women’s roles in the family than their non-migrant counterparts. We interpret our findings as strategic gender egalitarianism, that is, gender egalitarianism born of necessity, particularly economic necessity. Strategic gender egalitarianism does not, however, challenge dominant gender structures that define family relationships and allocate power unequally.